(untitled) (Modern Problems of Metallurgy, 2022)
Purpose: experimental study of the movement of vibrating screen elements with an elastic sieve.Research methods: determination of accelerations of vibrating screen elements using accelerometer sensors.An experimental study of the movement of vibrating screen elements was performed and the main kinematic characteristics were determined.The scheme of the measuring complex is developed, in the conditions of laboratory vibrating screen operation (oscillation frequency 25 Hz, maximum amplitude 4 mm). The measuring device uses the connection of 2 MPU 6050 or ADXL345 sensors to an Arduino Nano or STM32F103 microcontroller. The measurement limit of these sensors is within ± 16g, which corresponds to the parameters of the vibrating screen.It should be noted that the increase in amplitude (when the natural frequency of oscillation coincides with the frequency of oscillation of the screen) for different directions does not coincide in time. From this we can conclude that the natural frequencies of oscillations for different directions have the following ratio of free frequencies of oscillations fy> fz> fx.Analyzing the obtained data, we can conclude that the elastic elements of the sieve oscillates with an amplitude of 2-2.5 times greater than the amplitude of oscillations of the actual vibrating screen. In the vertical plane, the increase in amplitude reaches values of 1.9-2.1. This should contribute to better segregation of the material on the sieve and, accordingly, have a positive effect on the efficiency of sieving.In the direction of movement of the material, the increase in the amplitude of oscillations reaches 2.5 times at the time of run-out.In the transverse direction, the increase in amplitude is negligible, as the stiffness in this direction is very high.